AN EFFECTIVE MECHANISM OF MONETARY POLICY, BASIC TAXONOMY FUNCTIONING - N. Gryzunova; A. Aliev (Вестник Северо-Кавказского федерального университета, 2022)
The essence of monetary policy is to develop measures to regulate the money market in order to stabilize the economy and shallow cyclical processes. Money is the state's circulatory system. However, the state of Russian monetary policy can hardly be called healthy, despite the declared low inflation. Stimulating monetary policy is applied during a crisis, economic downturn and involves the growth of transfers, government purchases, tax adjustments - they must be balanced with government spending. Macroeconomic unpleasant surprises of soft monetary policy are traditional: an increase in excess reserves, an increase in the reserve ratio, and a decrease in the effectiveness of monetary incentives. It is necessary, as in everything else, an innovative approach to management, in determining the rules of monetary policy. New technologies are based on the processes of clustering of credit organizations, control of costs and prices, encouragement of competition, pursuing an income policy to stimulate an increase in demand for investment goods. However, in the current year, 2021 fiscal policy is able to provide faster and more significant help to the economy than monetary policy, on the other hand, the selected rate of monetary policy and budget regulations.